Association of non-high-density lipoprotein cholesterol to high-density lipoprotein cholesterol (NHHR) and sarcopenia in elderly adults - Yi Lin; Xiaocong Shi; Weijia Wu; Xiyi Chen (Frontiers in Nutrition)
BackgroundThis study aimed to explore the link between non-high-density lipoprotein cholesterol to high-density lipoprotein cholesterol ratio (NHHR) and sarcopenia in elderly adults using data from the National Health and Nutrition Examination Survey (NHANES).MethodsThe dataset from NHANES 1999–2004. Different statistical analyses, including logistic regression, restricted cubic spline, two-piecewise linear regression, subgroup analyses, and interaction tests models, were used to examine the relationship between NHHR and the risk of sarcopenia.ResultsTotal 3,190 elderly participants were included and 676 (21.2%) of them had sarcopenia. In crude model, the odds ratio (OR) of NHHR on sarcopenia was 0.71 [95% confidence interval (CI), 0.66–0.77]. After adjusting for all factors, the ORs for NHHR tertiles 2 and 3 were 0.76 (95% CI: 0.58–0.99) and 0.70 (95% CI: 0.53–0.94), respectively, with a significant trend (p = 0.014). An L-shaped relationship between NHHR and sarcopenia was found (P for non-linearity = 0.046), with 3.01 being the inflection point. Subgroup analysis results indicated a stable and persistent association between NHHR and sarcopenia across multiple subgroups, with the exception of diabetes.ConclusionWe found that NHHR was negatively associated with risk of sarcopenia in elderly adults.